Design of Fast-Charging Profiles for the Porsche Taycan EV Battery Module Based on Electrothermal Model and Extensive Testing - Uwalaka, Lucia (My University, 2024)
Fast charging technology is crucial for improving consumer acceptance and rapid adoption of electric vehicles (EVs), but it also poses significant thermal management challenges such as reduced battery life when left uncontrolled, performance degradation, and most importantly, the possibility of thermal runaway. To address these challenges and further improve the competitive advantage of EVs against their internal combustion engine (ICE) counterparts, most EV manufacturers are equipping their vehicles with fast-charging capabilities. It is certain that temperature is a major limiting factor to the fast-charging capabilities of EVs. Therefore, this thesis addresses this challenge of fast-charging profile design by proposing an efficient electrothermal model to predict temperature rise for any fast-charging profile. The primary goal is to develop a method that generates the optimal fast-charging profile, while reducing charging time and minimising the battery temperature rise. The electrothermal model is designed using a second-order Thevenin equivalent circuit model (ECM) combined with a simplified electrical equivalent circuit thermal model, whose parameters are obtained from cell characterisation and extensive battery module testing. Using this model, a wide range of current profiles is solved, and the optimal profile is determined. Finally, selected profiles are verified through experimental testing on a battery module. Compared to the reference fast-charging profile used in the production EV, the fastest profile achieved a 3% reduction in charging time with a reduction of 0.7°C in maximum temperature.
Keywords: Electric Vehicles; Fast Charging; Current Profile Design; Battery Module; Battery Testing